The effect of leadership and internal communication on job satisfaction at PDAM Tirta Giri Nata, Cirebon - Atiana, Sari; Siswanto, Siswanto (Universitas Negeri Yogyakarta, 2024)
The purpose of this study is to investigate how internal communication and leadership affect work satisfaction at PERUMDA Tirta Giri Nata in Cirebon City. This study's research methodology is a quantitative approach. With a sample of 66 workers, the population under study consisted of 190 employees of PERUMDA Tirta Giri Nata Cirebon City. A questionnaire was employed for data collection, and multiple analytic regressions were used to analyze the data. The study's findings demonstrated that leadership and internal communication were positively and significantly impacted at the same time. Internal communication had a positive and substantial impact on job satisfaction with a value of (2,296 > 1.99773) and a significant value of (0.025 < 0.05), whereas work on job satisfaction had a calculated value of (10,046 > 1,99773) and a significant value of (0.000 < 0.05). The F test, which was derived from the test results of 79.179 > 3.140 and a significant value of 0.000 < 0.05, revealed the simultaneous test between leadership and internal communication on job satisfaction at PDAM Tirta Giri Nata Cirebon City. This indicates that both leadership and internal communication had a positive and significant impact on job satisfaction.Keywords: Financial Technology, Development, Local MSMEs, Balinese People, QRIS